The 9th IEEE International Conference on E-Commerce Technology and the 4th IEEE International Conference on Enterprise Computin 2007
DOI: 10.1109/cec-eee.2007.16
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Framework for Outsourcing Governance

Abstract: Outsourcing has become a trend for a business to pursue short-term operational efficiency and long-term strategic competency by delegating IT infrastructure, applications, and even business processes to external service providers. At the same time, new challenges are emerging along with outsourcing such as what are the right services that should be outsourced, how well these services get performed, what benefits outsourcing brings in, and so on. Thus, effective service governance and management mechanisms for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The offering and acquisition of commoditized activities is the first phase of the process of implementing a successful outsourcing arrangement (Fan, Xiao, Shun, & Ji, 2007). Many researchers have suggested that organizations use their service providers as sources of external knowledge that positively influences their AC, and consequently the generation of innovations (Bahli, Wettenberg, Borgman, & Heier, 2013;Gonçalves, 2016;Lacity, 2017;Liang, Wang, Xue, & Cui, 2016;Weeks & Feeny, 2008).…”
Section: Outsourcing Of Information Technologymentioning
confidence: 99%
“…The offering and acquisition of commoditized activities is the first phase of the process of implementing a successful outsourcing arrangement (Fan, Xiao, Shun, & Ji, 2007). Many researchers have suggested that organizations use their service providers as sources of external knowledge that positively influences their AC, and consequently the generation of innovations (Bahli, Wettenberg, Borgman, & Heier, 2013;Gonçalves, 2016;Lacity, 2017;Liang, Wang, Xue, & Cui, 2016;Weeks & Feeny, 2008).…”
Section: Outsourcing Of Information Technologymentioning
confidence: 99%
“…Moreover, the RACI charts has been employed in outsourcing (Ramakrishnan & Pro, 2008;Simonova & Zavadilova, 2011) and managing governance in outsourcing (Meng, He, Yang, & Ji, 2007) too. While these governance frameworks use RACI to assign various roles and responsibilities in completing tasks or deliverables, in COBIT, its implementation is too generic for practical use (Zhang & Le, 2013).…”
Section: Lack Of Guidelinesmentioning
confidence: 99%
“…Since governance brings in responsibilities, allocation of responsibilities in the form of RACI charts has also been used for managing governance in outsourcing (Meng et al, 2007;Ramakrishnan & Pro, 2008;Simonova & Zavadilova, 2011). The RACI matrix used in outsourcing captures cross-vendor dependencies, and defines roles and responsibilities for all vendors (Ramakrishnan & Pro, 2008).…”
Section: It Outsourcing and Its Governancementioning
confidence: 99%